Evaluating the use of predatory insects as bioindicators of metals contamination due to sugarcane cultivation in neotropical streams - Corbi, Juliano Jose; Froehlich, Claudio Gilberto; Trivinho-Strixino, Susana; Santos, Ademir dos [UNESP] (Springer, 2011)
Streams located in areas of sugarcane cultivation receive high concentrations of metal ions from soils of the adjacent areas causing accumulation of metals in the aquatic sediment. This impact results in environmental problems and leads to bioaccumulation of metal ions in aquatic organisms. In the present study, metal concentrations in different predatory insects were studied in streams near sugarcane cultivation and compared to reference sites. Possible utilisation of predatory insects as bioindicators of metal contamination due to sugarcane cultivation from 13 neotropical streams was evaluated. Ion concentrations of Al, Cd, Cr, Cu, Zn, Fe, and Mn in adult Belostomatidae (Hemiptera) and in larvae of Libellulidae (Odonata) were analysed. Nine streams are located in areas with sugarcane cultivation, without riparian vegetation (classified as impacted area) and four streams were located in forested areas (reference sites). Metal concentrations in insects were higher near sugarcane cultivations than in control sites. Cluster analysis, complemented by an ANOSIM test, clearly showed that these insect groups are good potential bioindicators of metal contamination in streams located in areas with sugarcane cultivation and can be used in monitoring programmes. We also conclude that Libellulidae appeared to accumulate higher concentrations of metals than Belostomatidae.
Keywords: Metals; Streams; Libellulidae; Belostomatidae; Sugarcane cultivation